Zur Vegetationsdynamik im mediterranen Südfrankreich.: Internationaler Forschungsstand und erste Skizze zur Vegetationsdynamik im Raum Nimes (Frankreich/Dept. Gard) - Neff, Christophe; Frankenberg, Peter (ERDKUNDE, 1995)
The climax-concept of a sclerophyllous oak forest, with Quercus ilex as dominant species in the Mediterranean area, is more and more brought into doubt within international ecosystem research. But those results have not found a substantial reception in German vegetation geography. In German manuals the zonal vegetation of the Mediterranean region is still defined as sclerophyllous oak forest with Quercus ilex, in accordance with BRAUN-BLANQUET (1936). More recent research, such as that published by ROMANE a. TERRADAS (1992), has not gained much attention in Germany. ROMANE a. TERRADAS explain the dominance of Quercus ilex as a consequence of human impacts during the Neolithic period. For the Bas-Languedoc the authors have found similar results from analysis of the literature and from their own investigations. Those investigations are based on L. TRABAUD'S model, which is internationally recognized, but which is largely unknown in Germany. For those reasons L. TRABAUD'S model is briefly described (Fig. 1). In the two following models, the authors try to describe the principal processes in the dynamics of the vegetation and cultural landscape of the Nimes region. During the Neolithic period, the image of the landscape was substantially changed by human impacts. Those processes were probably reinforced during the Chasseen, and their consequences mainly affected the character of the landscape until the Industrial Revolution. During the Chasseen, the fertile and moist lands had been transformed into arable land, dislodging Quercus pubescens. In the remaining areas, which were episodica1ly or periodically used for hunting, ranging and exploiting fuelwoods, Quercus ilex was pushed into a dominant position. This process is also related to the large ecological performances of Quercus ilex. The rural exodus, one of the consequences of industrialization, was mainly reinforced by the melioration of the coastal plains for the returning colonists from the former French Algeria and by the consequences of coastal mass tourism at the seaside. This reinforced exodus not only attained the peripheral mountains, but also reached other large areas; and this reinforced rural exodus provided large areas of partly inhabited bush land. The first results of this large natural succession experiment are often in contradiction to classical climax theories. Following the climax theory, those areas should have been recolonised by Quercus ilex. For the Nimes region, the authors found examples for the remarkable population dynamics of Quercus pubescens on deeper substrata and the impressive competition force of Pinus pinea on Pleistocene gravels in the Costieres. Finally, the results of the vegetation dynamics are discussed by reference to the occurrence of fire ecology and compared with the objection raised by HEMPEL (1990) concerning the evolution of the cultural landscape in Greece. The authors also explain their prospective research aims in Mediterranean France, including fire ecology, old field successions, and problems of fuelwood exploitation and their role in the historic evolution of vegetation dynamics.